(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This paper involves batch and flow injection spectrophotometric determination of procaine-hydrochloride in pharmaceutical formulations. These methods were based on the diazotization reaction of procaine-HCl with sodium nitrite and hydrochloric acid to form diazonium salt, which is coupled with 8-hydroxyquinoline in alkaline medium to form orange-pink water soluble azo dye that was stable and has a maximum absorption at 509 nm. In batch method Beer’s law was obeyed in the concentration range of (0.8 - 8.0 µg/mL) and detection limit of 0.12 µg/mL with a correlation coefficient (r) of 0.9954 and a molar absorptivity of 2.0814x104 L mol-1cm-1. The flow injection analysis (FIA) system was applied for determination of procaine-HCl. The calibration graph is linear in the concentration range of (2.0 – 50 µg/mL) with detection limit (0.75 µg/mL) and correlation coefficient of (0.9927). The precision and accuracy of both methods were checked by calculating relative standard deviation (RSD) and relative error (E %) for two different levels of concentration.